2015
DOI: 10.2319/052015-343.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of micro-osteoperforation and corticision on the rate of orthodontic tooth movement in rats

Abstract: Objective: To investigate the effects of flapless micro-osteoperforation and corticision on the rate of orthodontic tooth movement in rats. Materials and Methods: Forty-five 8-week-old male Sprague-Dawley rats were divided into the following groups: micro-osteoperforation and orthodontic force (MOP + F), corticision and orthodontic force (C + F), and orthodontic force only (F, control). The left maxillary first molars were pulled forward with a force of 50 g. Flapless surgical interventions were conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 15 publications
7
33
0
1
Order By: Relevance
“…Tsai et al recently reported that MOP-facilitated ATM resulted in decreased root resorption upon H&E analysis. 40 Similarly, while half of the H&E samples in our study showed moderate root resorption on the MOP side, our volumetric analysis of all five roots of the maxillary first molar showed no significant increase in root resorption with MOPs, suggesting that MI-faciliated MOPs induced ATM without causing significant adverse effects on roots. A larger sample size however, is needed to further validate this finding.…”
Section: Discussionmentioning
confidence: 41%
“…Tsai et al recently reported that MOP-facilitated ATM resulted in decreased root resorption upon H&E analysis. 40 Similarly, while half of the H&E samples in our study showed moderate root resorption on the MOP side, our volumetric analysis of all five roots of the maxillary first molar showed no significant increase in root resorption with MOPs, suggesting that MI-faciliated MOPs induced ATM without causing significant adverse effects on roots. A larger sample size however, is needed to further validate this finding.…”
Section: Discussionmentioning
confidence: 41%
“…Among the surgery-assisted techniques, MOP is a new method to accelerate orthodontic tooth movement through small perforations in the alveolar bone without introducing great surgical trauma. The application of MOP in animal models has shown that small and shallow perforations in the alveolar bone increased the rate of tooth movement without requiring raising flaps, bone graft, or suture [23,24]. In comparison with the traditional orthodontics, a clinical study over a 1-month period has shown that when perforations are made to one side of the maxilla, the procedure significantly increased the rate of tooth movement by 2.3-fold, causing little pain or discomfort to the patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al 13 found that the amount of OTM increased to 4.41 times and 2.44 times in the maxilla and mandible, respectively, after applying 24 decortication dots with flap surgery in dogs. Tsai et al 14 found that the rate of OTM was 1.54 and 1.49 times as fast in a corticision group and micro-osteoperforation group, respectively, than in the control, showing no difference between the two flapless procedures. In the current study, it was found that flapless osteoperforation facilitated OTM by 1.81 times even through the atrophic ridge in the beagle mandible over 10 weeks.…”
Section: Discussionmentioning
confidence: 99%